Chapter How to become a pastry chef: a statistical analysis through the company requirements - Mariani, Paolo (Proceedings e report, 2021)
The definition of requested requirements by the companies represents one of the key aspects for the entrance of new professional figures. In particular, focusing the attention on food & beverage sector, in this study two job profiles are considered: pastry chef e pastry assistant. Data for this analysis are collected by The AdeccoGroup in Italy in 2016 and 2017. The personal competencies to make capable to face the growing flexibility of the profession are object of specified request cross-sectional to more economic sectors. After a brief description of the database content, the principal objective of the research is to report the most requested requirements for the companies. Other analysis are provided to show possible relationships among these requirements and the previous experience owned by candidates. Finally, a comparison is presented about the competencies requested by the two job figures using descriptive statistics and classification techniques.